Formation and speciation of Sullage Water Natural Conduct analysis of Fuzzy logic Application by Solar Distillation - Shanmugan, S; P, Selvaraju; Karthickeyan, M; Saravanan, A; Akash Kanna, G; Ranjith Raja, V (International Journal of Engineering and Technology, 2018)
The recital analysis of thermal techniques for sullage water treatment and fuzzy logic techniques are used to harvest clean water, drinkable water (H2O), fertilizer, ash impurity adding with cement from sullage water by using the energy of the sun. The experimental analysis of sullage water process is implemented of strong luminous that diurnal with weather condition in Vel Tech Multi Tech Dr. Rangarajan Dr Sakunthala Engineering College. It is an innovation to reduce the fluid waste and called water quality conversion. The suspended fluid waste changes the excellence of pure water and ash by thermal and fuzzy logic techniques. In this work is to analyze and compare between pure water and sullage water. It is analyzed of one of the days in the system have been given the 24 hr cycle, the total drip production of the proposed system is found to be 7.324 kg/m2day and without drip 4.952 kg/m2day and Overall efficiency is 36%.Â